Advisors Reports for Annual Plan 1987-1988 All States/Union Territories - Planning Commission (Planning Commission, 1987)
Another point worth mentioning in this regard is the fact that the latest assessed resources of Rs. 1000.32 crores for .the current year do not provide for the liability of Rs. 33 crores by the State Government for flood relief. The State Government in its Memorandum have pleaded for the current year’s flood being treated as one of rare severity and position of 100% assistance as recommended by the Finance Commission in cases of exceptional severity. In case, this is not agreed to, the current year’s anticipated surplus of Rs. 0.32 crore will be converted into a deficit of Rs, 32.68 crores.
Planning Commission, State Plan Division
Planning Commission